2006
DOI: 10.1186/1749-8090-1-2
|View full text |Cite
|
Sign up to set email alerts
|

Variations in clinical decision-making between cardiologists and cardiac surgeons; a case for management by multidisciplinary teams?

Abstract: Objective: To assess variations in decisions to revascularise patients with coronary heart disease between general cardiologists, interventional cardiologists and cardiac surgeons Design: Six cases of coronary heart disease were presented at an open meeting in a standard format including clinical details which might influence the decision to revascularise. Clinicians (n = 53) were then asked to vote using an anonymous electronic system for one of 5 treatment options: medical, surgical (CABG), percutaneous coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 18 publications
0
23
1
Order By: Relevance
“…18 In New York State, Hannan and colleagues observed that many pa tients who had indications for CABG surgery (according to the American College of Cardiology / American Heart Association guidelines) at the time of angiography received multivessel PCI and never saw a cardiac surgeon. 19 Although previous studies have shown that interventional cardiologists are more likely to recommend PCI and cardiac surgeons are more likely to recommend CABG surgery for patients with similar indications, 20,21 we found substantial variation among cardiology specialists across different hospitals in terms of their revascularization practices.…”
Section: Discussioncontrasting
confidence: 43%
“…18 In New York State, Hannan and colleagues observed that many pa tients who had indications for CABG surgery (according to the American College of Cardiology / American Heart Association guidelines) at the time of angiography received multivessel PCI and never saw a cardiac surgeon. 19 Although previous studies have shown that interventional cardiologists are more likely to recommend PCI and cardiac surgeons are more likely to recommend CABG surgery for patients with similar indications, 20,21 we found substantial variation among cardiology specialists across different hospitals in terms of their revascularization practices.…”
Section: Discussioncontrasting
confidence: 43%
“…Multidisciplinary decision-making in a Heart Team can minimize specialty bias and prevent self-referral from interfering with optimal patient care. 49 Several reports from different centres have established that the treatment recommendations made in multidisciplinary Heart Team discussions are reproducible and implemented in the vast majority of cases (93-95%). 50,51 Interdisciplinary institutional protocols should be developed for common case scenarios to avoid the need for systematic caseby-case review of all diagnostic angiograms.…”
Section: Multidisciplinary Decision-making (Heart Team)mentioning
confidence: 99%
“…Moreover, Heart Team seems to be an "ideal platform for recruitment into trials of PCI vs CABG" as SYNTAX teams proved to be [51]. In addition, not all the hospitals detain on-site cardiac surgery, which makes the decisions biased toward PCI [52] (a situation almost similar to the contrary situation, as surgeons show a slight bias toward CABG) [53,54].…”
Section: Cardiovascular Erapeuticsmentioning
confidence: 99%